2020
DOI: 10.1101/2020.10.26.20219428
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Community prevalence of SARS-CoV-2 in England during April to September 2020: Results from the ONS Coronavirus Infection Survey

Abstract: Background: Decisions regarding the continued need for control measures to contain the spread of SARS-CoV-2 rely on accurate and up-to-date information about the number of people and risk factors for testing positive. Existing surveillance systems are not based on population samples and are generally not longitudinal in design. Methods: From 26 April to 19 September2020, 514,794 samples from 123,497 individuals were collected from individuals aged 2 years and over from a representative sample of private house… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
1
10
0
1
Order By: Relevance
“…This has recently also been proposed on the basis of theoretical work linking effective reproduction numbers to population level Ct[26]. For example, declines in mean and median Ct values were apparent throughout August ( Figure 1B ), although positivity rates in the survey were only noted to increase in early September[9]. Ct data are widely available within laboratory management systems and could be used alongside available risk factor and symptom information to facilitate more informed and effective individual-level and public health responses to the SARS-CoV-2 pandemic.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This has recently also been proposed on the basis of theoretical work linking effective reproduction numbers to population level Ct[26]. For example, declines in mean and median Ct values were apparent throughout August ( Figure 1B ), although positivity rates in the survey were only noted to increase in early September[9]. Ct data are widely available within laboratory management systems and could be used alongside available risk factor and symptom information to facilitate more informed and effective individual-level and public health responses to the SARS-CoV-2 pandemic.…”
Section: Discussionmentioning
confidence: 55%
“…However, number of genes detected and symptoms are both potential mediators of effects of demographic factors ( Supplementary Figure 2 ); and there were strong effects of calendar time on positivity in different demographic subgroups[9] and on Ct values ( Figure 1A ). Excluding the potential mediators (number of genes detected, symptoms) and adjusting for visit date, Ct values remained independently lower (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings contrast with the repeated cross-sectional REACT2 study,[23] which reported greater reductions over time at a population-level in the proportion of adults ≥65 years testing antibody-positive, and more sustained responses in those 18-24 years. Nearly all HCWs in our study were <65 years, other differences may arise from study design, the assay used, and the potential for new infections predominantly in younger people[24] to replace others who had sero-reverted, supporting population-level seroprevalence (in our study these individuals are followed separately). Ongoing longitudinal studies are required to determine the long-term kinetics of antibody-mediated response to SARS-CoV-2, and responses to re-exposure.…”
Section: Discussionmentioning
confidence: 80%
“…We used three datasets to validate our models: the Office for National Statistics (ONS) Community Infection Survey, the Real-time Assessment of Community Transmission (REACT-1) study, and UK Government testing data. The ONS survey 7 is a longitudinal survey of individuals selected to be a representative sample of private households (excluding eg, care homes and student accommodation), which began on April 26, 2020. Individuals in the ONS survey are supervised while they self-administer nose and throat swabs.…”
Section: Methodsmentioning
confidence: 99%